The efficacy of disinfecting contaminated screws with chlorhexidine 0.5%, povidone-iodine 10% and alcohol 70% - Sandhu, Arunjit Singh (2022)
Introduction The inevitability of dropping an implant, graft or other surgical instruments during a surgery onto the surgical floor is unavoidable. Most of the times there will always be a replacement available. However there are times in which a surgeon needs to reuse a graft or implant that has been on the floor, and reuse it for the patient after decontamination has been done. In the past decontamination was done with the use of povidone iodine. The current recommendation method for decontamination currently is chlorhexidine. Decontamination can be achieved by the use of 10% povidone iodine, chlorhexidine 0.5% and alcohol 70%. The objective of this study is to determine the efficacy of disinfecting contaminated screws with 0.5% chlorhexidine, 10% povidone-iodine, 70% alcohol. Materials and methods This was a prospective study performed at Hospital Raja Perempuan Zainab 2. A total of 134 sterilized screws were used and autoclaved before being distributed into 4 groups, control positive, 0.5% chlorhexidine, 10% povidone-iodine, 70% alcohol. Each screw was dropped 1 hour into surgery.the screws were dropped from a 1 meter height. Screws that were at a 1 meter diameter around the operation table were allowed to rest on the floor for 30 seconds before being picked up with sterile forceps. The screws were then placed in their respective solutions for 10 minutes before being cleaned with a sterile gauze. Each screw were then placed into its own nutrient broth media and sent to the lab to see if they yield any growth. Results There were a total of 134 screws dropped and were divided into groups of 34 screws each. The results that were obtained from the lab revealed: 1) Control positive 31(91.1%) growth 2) 10% povidone iodine, 24(70.5%) growth, p 0.040 3) Chlorhexidine 0.5% 3(8.8%) growth, p <0.001 4) Alcohol 70% 30(88.2%) growth, p 0.691 Conclusion From this study, it was found that chlorhexidine p<0.001 was the most superior solution that can be used for decontamination. This finding is consistent with most of the studies that have been done in the past revealing that chlorhexidine was superior. Povidone iodine p 0.040 was once a solution of choice but it is evident that it’s not superior to chlorhexidine from this study. Therefore we suggest the use of chlorhexidine as a solution for decontamination should the need ever arise.